The Shifting Appreciation of "Hamlet" in Its Japanese Novelizations: Hideo Kobayashi’s "Ophelia’s Will" and Its Revisions - Nakatani, Mori (Multicultural Shakespeare: Translation, Appropriation and Performance, 2020)
Hideo Kobayashi, who is today known as one of the most prominent literary critics of the Showa era in Japan, published Ophelia’s Will in 1931 when he was still an aspiring novelist. This novella was an adaptation of Shakespeare’s Hamlet, composed as a letter written by Ophelia to Hamlet before her enigmatic death in the original play. While the novel has previously been considered as a psychological novel that sought to illustrate the inner life of the Shakespearean heroine, this paper examines the process by which Kobayashi rediscovered Hamlet as a drama that foregrounds the impenetrability of the characters’ inwardness and highlighted in Ophelia’s Will his diversion from the psychological rendition of Ophelia. In so doing, the paper analyses the revisions Kobayashi continued to make to the novel even until the post-war era, especially when it was republished in 1933 and 1949. Though these revisions have rarely been discussed by the researchers, they demonstrate the essential changes made to the novel, mainly to its literary style, which corroborates Kobayashi’s shifting interest and his developing interpretation of Shakespeare’s works and Hamlet.